Rates of Wintertime Atmospheric SO2 Oxidation based on Aircraft Observations during Clear‐Sky Conditions over the Eastern United States. Issue 12 (24th June 2019) - Green, Jaime R.; Fiddler, Marc N.; Holloway, John S.; Fibiger, Dorothy L.; McDuffie, Erin E.; Campuzano‐Jost, Pedro; Schroder, Jason C.; Jimenez, Jose L.; Weinheimer, Andrew J.; Aquino, Janine; Montzka, D. D.; Hall, Samuel R.; et al.
Abstract: Sulfur dioxide (SO2 ) is emitted in large quantities from coal‐burning power plants and leads to various harmful health and environmental effects. In this study, we use plume intercepts from the Wintertime INvestigation of Transport, Emission and Reactivity (WINTER) campaign to estimate the oxidation rates of SO2 under wintertime conditions and the factors that determine SO2 removal. Observations suggest that OH governs the rate SO2 oxidation in the eastern United States during winter. The range of mean oxidation rates during the day from power plants were 0.22–0.71%/hr, producing SO2 lifetimes of 13–43 days, if SO2 consumption is assumed to occur during 10.5 hr of daylight in cloudless conditions. Though most nighttime rate measurements were zero within uncertainty, there is some evidence of nighttime removal, which suggests alternate oxidation mechanisms. The fastest nighttime observed SO2 oxidation rate was 0.25±0.07%/hr, producing a combined day/night SO2 lifetime of 8.5–21 days. The upper limit of the oxidation rate (the mean+1 σ of the fastest day and night observations) is 16.5%/day, corresponding to a lifetime of 6.1 days. The analysis also quantifies the primary emission of sulfate from power plants. The median mole percentage of SO4 ‐2 from observed plumes was 1.7% and the mean percentage sulfate was 2.8% for intercepts within 1 hr of transit to power plants. The largest value observed from close intercepts was over 7% sulfate, and the largest extrapolated value was 18%, based on intercepts further from their source and fastest observed oxidation rate. Key Points: The daytime conversion rate of SO2 to SO4 ‐2 was 0.22‐0.71%/hr in winter under clear‐sky conditions, with lifetimes of 140‐450 hr For 10.5 hr of daylight, the upper limit of the oxidation rate is 16.5%/day, corresponding to a lifetime of 6.1 days Direct emissions of SO4 ‐2 relative to total sulfur (SO2 + SO4 ‐2 ) had mean and median values of 1.7% and 2.8%, respectively